Improving learnability and understandability of a Web application using an action-based technique - Zamli, Kamal Zuhairi (2011)
The emergence of the Internet era leads to the widely used of Web-based applications. Diverse demographic of users requires Web applications to have the features that enable different level of users to learn and understand their functionalities easily and instantly. Thus, a Web application that is learnable and understandable allows users to interact better and gain more advantages of using the Web application. Users' interactions with a system often reflect users' knowledge and understanding of the system. By studying users' interactions, Web developers can provide guidance to users, which promote the learnability and understandability of a Web application. The aim of this paper is to improve usability in the aspects of learnability and understandability through user interface design of a Web application. This paper proposes an action-based technique to improve users' learnability and understandability by studying users' interactions while they are interacting with the user interface of a Web application. Web developers can apply the proposed technique in designing a more usable Web application in the future.